COMPARATIVE ANALYSIS OF MATURE AND PREPROPROTEIN FORM OF THIONINS IN SOME PLANT SPECIES; BIOINFORMATICS APPROACHES - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2019)
Thionins are one of the most important antimicrobial peptides in broad-range plant defense. A number of studies are present regarding the structural and biological role of mature thionins but preproprotein forms of these molecules have not been extensively studied. Thus, this study aimed to comparatively analyze a total of 56 thionin preproprotein sequences from 14 different plant species. Analyses of primary, secondary and tertiary structures of these forms revealed that preproproteins with gamma-thionin domain were relatively shorter and more basic than proteins with thionin domain structure. In addition, members of thionin domain were more similar to each other than that of gamma-thionin domain forms. Sub-cellular localizations of these forms were predicted as extracellular. Structural superposition of precursor and mature thionins showed that a large portion of precursor sequences are cleaved to form a functional protein. Although precursor forms demonstrated the significant structural divergence in modelled species, functional mature forms showed a structural pattern in alpha-helices; two alpha-helix proteins included the thionin domain family while one a-helix proteins contained the gamma-thionin domain family. Results of this study will become valuable theoretical knowledge and provide insight in terms of further understanding the formation of mature functional thionins thereby their biological roles.
Keywords: alpha/beta-thionins; gamma-thionins; disulfide bridges; 3D modeling; plant defense; EUROPEAN MISTLETOE; EXPRESSING THIONIN; ANTIFUNGAL; RESISTANCE; DEFENSE; POTATO; WHEAT; PREDICTION; BARLEY